Alcohol Abuse Decreases Pelvic Control and Survival in Cervical Cancer: An Opportunity of Lifestyle Intervention for Outcome Improvement. (October 2017) - Mayadev, Jyoti; Li, Chin-Shang; Lim, Jihoon; Valicenti, Richard; Alvarez, Edwin A.
Abstract : Purpose: We examined the incidence and the effect of alcohol abuse on pelvic control (PC), disease-free survival (DFS), and overall survival (OS) in locally advanced cervical cancer patients undergoing definitive radiation therapy (RT). Methods: Between 2007 and 2013, 95 patients treated with RT were reviewed, and the tumor characteristics, the RT dose, the treatment time, chemotherapy, and the number of cycles were recorded. The association between alcohol abuse and DFS, OS, and the duration of PC was analyzed using multivariable Cox proportional hazards models. Results: Of the 95 patients with an average age of 54.8 years (range, 27 to 91 y), 30% were FIGO stage 1B1, 1B2, 2A, 52% stage 2B, 3A; and 18% stage 3B; 86% of the patients were treated with weekly cisplatin chemotherapy. Alcohol history showed that 10 (10.5%) patients met the CDC criteria for heavy alcohol use. With a mean follow-up time of 2 years, 85 patients (88.5%) achieved PC and 86 patients (90.5%) were free of distant metastasis. A total of 82 patients (86.3%) were alive at the last follow-up. When controlling for the total treatment time, excessive alcohol abuse was significantly associated with a decrease in DFS ( P =0.005; hazard ratio [HR], 6.19; 95% confidence interval [CI]: 1.73, 22.18), OS ( P =0.001; HR, 6.68; 95% CI: 2.10, 21.26), and PC ( P =0.029; HR, 3.10; 95% CI: 1.13, 8.56) on univariable analysis. On multivariable analysis, excessive alcohol abuse was significantly associated with a decrease in DFS ( P =0.005; HR, 10.57; 95% CI: 2.07, 53.93) and OS ( P =0.001; HR, 10.80; 95% CI: 2.57, 45.40). Conclusions: In this small hypothesis-generating series of patients with heavy alcohol use, the data support the association that heavy alcohol use increases the risk of cancer recurrence and mortality. Additional research is required to better define the patient- and treatment-related factors that may be targeted for intervention.